EFEKTIVITAS KOMUNIKASI PEMASARAN VIRTUAL TOUR DI MUSEUM KONPERENSI ASIA-AFRIKA KOTA BANDUNG - Indah Inayah, Resta; Kusuma Negara, I Made; Wijaya, NMS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 2 (2021): Jurnal IPTA (December 2021)DO - 10.24843/IPTA.2021.v09.i02.p16, 2021)
Virtual tours are a form of online communication marketing born in the era of the industrial revolution 4.0 due to the use of the internet of things as the backbone of movement and connectivity between humans and machines. This study aims to analyze the effectiveness of online communication marketing through a virtual tour on the Museum of the Asian-African Conference's website. The operational definition of the variables used was the AIDA variable consists of attention, interest, desire, and action with 14 total indicators. Data collection techniques used were observation, questionnaires, interviews, and literature studies. The researcher used the quota sampling technique by determining the number of samples taken was 100 respondents. The data analysis technique used was a quantitative descriptive analysis using the Customer Response Index (CRI) calculation. The results of this study indicate that the effectiveness of online communication marketing through a virtual tour on the website of the Museum of the Asian-African Conference has an average AIDA score of 3.28, which is on a scale range of 3.25 - 4.0 in a very effective way and has a CRI value of 50.7% of the overall measurement of respondents which means effective.